Reactive Astrocytes Derived From Human Induced Pluripotent Stem Cells Suppress Oligodendrocyte Precursor Cell Differentiation - Smith, Matthew D.; Chamling, Xitiz; Gill, Alexander J.; Martinez, Hector; Li, Weifeng; Fitzgerald, Kathryn C.; Sotirchos, Elias S.; Moroziewicz, Dorota; Bauer, Lauren; Paull, Daniel; Gharagozloo, Marjan; Bhargava, Pavan; et al. (Frontiers in Molecular Neuroscience, 2022)
Astrocytes are instrumental in maintaining CNS homeostasis and responding to injury. A major limitation of studying neurodegenerative diseases like multiple sclerosis (MS) is lack of human pathological specimens obtained during the acute stages, thereby relegating research to post-mortem specimens obtained years after the initiation of pathology. Rodent reactive astrocytes have been shown to be cytotoxic to neurons and oligodendrocytes but may differ from human cells, especially in diseases with genetic susceptibility. Herein, we purified human CD49f+ astrocytes from induced pluripotent stem cells derived from individual patient and control peripheral leukocytes. We compared TNF and IL1a stimulated human reactive astrocytes from 7 persons with MS and 6 non-MS controls and show their transcriptomes are remarkably similar to those described in rodents. The functional effect of astrocyte conditioned media (ACM) was examined in a human oligodendrocyte precursor cell (OPC) line differentiation assay. ACM was not cytotoxic to the OPCs but robustly inhibited the MBP reporter. No differences were seen between MS and control stimulated astrocytes at either the transcript level or in OPC suppression assays. We next used RNAseq to interrogate differentially expressed genes in the OPC lines that had suppressed differentiation from the human ACM. Remarkably, not only was OPC differentiation and myelin gene expression suppressed, but we observed induction of several immune pathways in OPCs exposed to the ACM. These data support the notion that reactive astrocytes can inhibit OPC differentiation thereby limiting their remyelination capacity, and that OPCs take on an immune profile in the context of inflammatory cues.